Níveis de suplementação de selênio e vitamina E para codornas de corte em crescimento - Zancanela, Vittor (2016)
Four experiments were carried out in order to determine the levels of supplementation of selenium (Se) inorganic or organic and vitamin E (VE) in diets of meat quails (Coturnix coturnix coturnix) in periods 0-14 and 14 to 35 days old. A completely randomized design was used in a 4x4 factorial design (Se = 0.1125; 0.2250; 0.3375 and 0.4500 mg/kg/diet x VE = 10; 23; 36 and 49 IU/kg/diet). In experiment 1 (inorganic Se), 0-14 days old, were used 2400 newborn quail, distributed in 16 treatments, three replicates and 50 birds per experimental unit. In experiment 2 (inorganic Se), 14-35 days, were used 1680 quails at 14 days de age, distributed in the same treatments, with three replicates of 35 birds per experimental unit. In the period 0-14 days the levels of VE did not affect the performance (P>0.05), however, the feed conversion (FC) was influenced in a quadratic effect (P = 0.0515), according to the level of Se, with a higher level estimated with 0.29 mg Se/kg/diet. In the period of 14-35 days there was a linear effect with interaction (SexVE), for FC (P=0.0150) and the weight gain (WG, P=0.0266). The FC (Se, P=0.0048) and (VE, P=0.0019), and the WG (Se, P=0.0049) and (VE, P=0.0068) improved linearly with increasing levels of Se and VE in diets. The feed intake (FI), decreased linearly (P=0.0582) in function of the levels of VE. The breast yield increased and decreased linearly in function to the levels of Se (P=0.0501) and vitamin E (P=0.0220) respectively used. The carcass yield showed a quadratic effect (P=0.0056) in function to the levels of VE used, with estimation of higher yield of 27.24 IU of VE/kg/diet. There was a significant interaction (P=0.0123) with a linear increase in brightness (L*) of the meat, depending on the levels of Se (P = 0.0328 ) and left ventricle (P=0.0358) .The light component red-green (a*) presented a quadratic effect (P=0.0229), depending on the levels of Se. The point of 16.43 to the maximum red color was estimated with 0.28 mg Se/kg feed. The loss of defrosting water (PD) linearly reduced (P=0.0260) versus the levels of Se, and the loss of water for cooking (PC) showed a quadratic response (P=0.0422) versus the levels of VE. The lowest water loss by cooking (5.23g) was obtained with the level of 29.58 IU of VE/kg of feed. It was conclude that the level of supplementation for maximum performance of meat quails in the period 0-14 days of age is 0.29 mg/Se/kg/diet and 10 IU of VE/kg/diet, and from 14 to 35 days of age are recommended the maximum levels (0.4500 mg/Se and VE 49 IU/kg diet). In experiment 3 (organic Se), 0-14 days old, were used 2400 newborn quail, distributed in 16 treatments, three replicates and 50 birds per experimental unit. In experiment 4 (organic Se), 14-35 days, were used 1536 quails at 14 days de age, distributed in the same treatments, with three replicates of 32 birds per experimental unit. In the period 0-14 days of age, was not observed effect of Se and VE on bird performance (P>0.05). In the period 14-35 days old, the selenium levels have worsened the FC (P=0.0016) and linearly increased the FI (P=0.0224). The breast yields (P=0.0171) and legs (P=0.0695) showed a quadratic effect in function on the levels of Se in diets. There was a linear reduction in breast yield in function on VE (P=0.0126). The estimates of higher breast yield (45.37%) and legs (25.03%) were obtained with diets containing 0.25 and 0.32 mg Se/kg/feed. The luminance component (a*) increased linearly (P = 0.07) as a function of VE levels. The loss of defrost water (PD) presented a quadratic effect (P=0.0564) on the basis of VE levels. The lowest water loss (1.35g) was obtained with the level of 32.89 IU of VE/kg of feed. There was interaction (P=0.0288) between the levels of Se and VE for shear force (FC); with linear decrease depending on the levels of Se (P = 0.0092) and EV (P=0.0053). It was conclude that in both phases, the minimum levels of organic Se (0.1125mg/kg) and VE (10IU/kg) used in diets based on corn and soybean meal were sufficient to meet the requirements of quails.